Penerapan User Centered Design pada Perancangan Sistem Informasi Pelayanan Publik dengan Fitur Geospatial Visualization pada Layanan Aduan dan Fitur Chatbot Ai Studi Kasus Polres Tulungagung. - Adam Firmansyah; Yayak Kartika Sari; Taufiq Agung Cahyono (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
The public service information system at the Tulungagung Police Resort still faces various obstacles, such as an unresponsive interface, difficulty in accurately determining the location of incidents, and limited information services outside operating hours. This study aims to design and develop a web-based public service information system by applying the User Centered Design (UCD) method to improve user experience. The study uses the Research and Development (RnD) method with UCD stages that include user needs analysis, interface design, system development, and usability evaluation. Data were collected through observation, interviews, questionnaires, and documentation involving Tulungagung Police Resort service users. The developed system integrates the Geospatial Visualization feature to accurately map complaint locations and the Artificial Intelligence Chatbot feature as an automatic 24-hour information service. Data analysis was conducted descriptively quantitatively using Black Box Testing to test system functionality and the System Usability Scale (SUS) to measure the level of usability. The results showed that all system functions ran well with a validity level of 100%, and the usability value increased from 28.5 (Not Acceptable) to 78.75 (Acceptable–Good). These findings show that the system is capable of increasing the efficiency, accuracy, and quality of public services more optimally.